2010
DOI: 10.1111/j.1742-4658.2010.07814.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel G‐quadruplex motif modulates promoter activity of human thymidine kinase 1

Abstract: G‐quadruplex motifs constitute unusual DNA secondary structures formed by stacking of planar hydrogen‐bonded G‐tetrads. Recent genome‐wide bioinformatics and experimental analyses have suggested the interesting possibility that G‐quadruplex motifs could be cis‐regulatory elements. Here, we identified a characteristic potential G‐quadruplex‐forming sequence element within the promoter of human thymidine kinase 1 (TK1). Our NMR, UV and CD spectroscopy and gel electrophoresis data suggested that this sequence for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 64 publications
3
23
0
Order By: Relevance
“…This sequence consists of consecutive GG-repeats with the potential to fold into a non-canonical G-quadruplex structure with two stacked guanine tetrads rather than the three tetrads that have commonly featured in most genomic G-quadruplexes. While some G-quadruplex motif search algorithms have been based on a minimum of three G-tetrads (34,37), biophysical experiments have supported G-quadruplex formation with just two tetrads, as it is the case for the thrombin binding DNA aptamer 5′-GGT TGG TGT GGT TGG-3′ (38) and more recently, a quadruplex motif within the promoter of human thymidine kinase 1 (39). …”
Section: Resultsmentioning
confidence: 99%
“…This sequence consists of consecutive GG-repeats with the potential to fold into a non-canonical G-quadruplex structure with two stacked guanine tetrads rather than the three tetrads that have commonly featured in most genomic G-quadruplexes. While some G-quadruplex motif search algorithms have been based on a minimum of three G-tetrads (34,37), biophysical experiments have supported G-quadruplex formation with just two tetrads, as it is the case for the thrombin binding DNA aptamer 5′-GGT TGG TGT GGT TGG-3′ (38) and more recently, a quadruplex motif within the promoter of human thymidine kinase 1 (39). …”
Section: Resultsmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14][15][16][17] Recently, there are also a few reports about the structures and biological functions of two-quartet G-quadruplexes, like the promoters of oncogene HIF1ɑ and TK1 57,58. Our findings suggest that more attentions should be paid to the structure and function of G 2 sequences.…”
mentioning
confidence: 83%
“…The program was rerun with cytosine (C) instead of guanine (G) to identify motifs on the complimentary strand and appropriately corrected for strand orientation. We restricted our program to a stem size of 3 and loop length of 1–7 considering that most in vitro characterizations and experiments have used these guidelines for PG4 motifs, though recent work shows that non-canonical motifs are also possible with varying loop and stem sizes (5,19,26). …”
Section: Methodsmentioning
confidence: 99%
“…Similarly, transcription was influenced by G-quadruplex-forming sequence motifs within the core promoter of human c- KIT (16) and k-RAS oncogenes (17). Promoter-G-quadruplex were also reported for a number of other genes such as VEGF , PDGF , HIF1α , BCL-2 , RB and RET (18) in addition to thymidine kinase 1 , where a non-canonical G-quadruplex motif formed from repeats constituting two guanines instead of three was found to be functionally active (19). In line with these studies, transcriptome profiling performed in human cancer cells indicated changes in gene expression in presence of established intracellular G-quadruplex binding ligands suggesting a genome-wide role of G-quadruplex motifs in transcription (20).…”
Section: Introductionmentioning
confidence: 95%